PENGARUH LITERASI KEUANGAN, PENDAPATAN, DAN TOLERANSI RISIKO TERHADAP PERILAKU KEUANGAN DAN DAMPAKNYA PADA KEPUTUSAN INVESTASI : STUDI KASUS GEERASI Z KOTA SEMARANG - Patricia Dhiana Paramita; Daniel Kartika Adhi; Nurkholik Nurkholik; Heru Sri Wulan; Izza Nisa’ul Afi (JURNAL LENTERA AKUNTANSI, 2025)
As a digitally savvy generation, Gen Z plays an increasingly significant role in Indonesia's capital markets, now comprising more than half of its investor base. This study applies a behavioral finance perspective to examine how financial knowledge and psychological traits influence investment outcomes. The objective of this study is to explore the impact of financial literacy, income, risk tolerance, and financial behavior on investment decisions among Generation Z in Semarang City. A quantitative approach  was used, with data collected  from 110 Gen  Z investors selected through purposive sampling. Respondents completed an online questionnaire measured on a five-point Likert scale, and the data were analyzed using SPSS. The analysis results show that financial literacy, income, risk tolerance, and financial behavior all have a positive and significant influence on investment decisions. This is supported by a significance value below 0.05 and a t-value above the critical value of 1.98260. Further analysis using the Sobel test evaluated the mediating role of financial behavior. The test produced a Z-score below the significance threshold of 1.96, indicating no significant mediation in  the tested  relationship. Thus,  although financial  behavior directly influences investment decisions, it does not mediate the influence of financial literacy, income, or risk tolerance. These findings highlight that financial literacy, income, and risk tolerance are the main factors shaping Generation Z's investment behavior, with financial behavior acting more as an outcome than an intermediary in this context.